Diagnotic Accuracy of Computed Tomography in Detection of Retinoblastoma (Journal of Fatima Jinnah Medical University, 2018)
Objective: to find out the accuracy of CT scan in diagnosing retinoblastoma with the gold standard of diagnosis being histopathology. Study design: It is a cross sectional study Done in the department of diagnostic radiology, Lahore general hospital, Lahore from 02-05-2013 to 01 -11 -2013. Patients and Methodology: This study comprised of 240 patients with clinical suspicion of retinoblastoma. Computed tomography on Toshiba Asteion VF Model TXS 021B/1N, Single Slice Helical, images in the axial, sagittal and coronal projections was obtained without l/V contrast. The cases were operated and histopathological results were recorded. The results of computed tomography and histopathology were compared taking histopathology as gold standard. Results: Out of 240 patients, 135 patients (56.25%) had retinoblastoma computed tomography. After comparison of results of computed tomography with histopathology, the sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of computed tomography were 87.14%, 90.48%, 92.19%, 84.82% and 88.75% respectively. Conclusion: CT scanning with a sensitivity of 87.14% and a specificity of 90.48% in the diagnosis of retinoblastoma should be considered a worthwhile modality. It provides an edge in diagnosis with its accurate depiction of even the smallest calcifications. The earlier the detection, the earlier will be the treatment and its effectiveness.
Keywords: Retinoblastoma, Computed Tomography